Processes in the area of laser beam exposure to metal research during laser welding in vacuum - Letyagin, I.Yu.; Belenkiy, V.Ya.; Lyamin, Ya.V.; Erikov, A.P. (Perm Federal Research Centre Journal, 2019)
Research results are presented of secondary emission signals in the zone of interaction of a laser beam with metal in order to study the possibility of monitoring the process of formation of laser weld in vacuum. Experimental studies of the parameters of the secondary emission electron and ion currents during pulsed laser welding in vacuum have been carried out. The dependences of the parameters of the secondary emission signals from the laser welding zone in vacuum on the distance between the collector of charged particles registering these signals and the product being welded, as well as the effect of the degree of vacuuming of the process chamber on the parameters of the secondary emission signals, are investigated. The results of the research will make up the basis for the development of methods of secondary emission control of the process of weld formation during laser welding in vacuum; its implementation into industrial production will ensure high reproducibility of the quality of welded joints produced by laser welding in vacuum and the absence of defects in welds.